Portraits of American politics - Murphy, Bruce Allen (Houghton Mifflin, 2000)
Popular and compelling, this reader provides biographical accounts of key players in America's political history. The narratives in the text focus on individuals and the roles they play in political institutions and events, adding a human element to the American political scene.